Training the gut for athletes - Jeukendrup, A. E. (Sports Medicine, 2017)
The gastrointestinal (GI) tract plays a critical role in delivering carbohydrate and fluid during prolonged exercise and can therefore be a major determinant of performance. The incidence of GI problems in athletes participating in endurance events is high, indicating that GI function is not always optimal in those conditions. A substantial body of evidence suggests that the GI system is highly adaptable. Gastric emptying as well as stomach comfort can be "trained" and perceptions of fullness decreased; some studies have suggested that nutrient-specific increases in gastric emptying may occur. Evidence also shows that diet has an impact on the capacity of the intestine to absorb nutrients. Again, the adaptations that occur appear to be nutrient specific. For example, a high-carbohydrate diet will increase the density of sodium-dependent glucose-1 (SGLT1) transporters in the intestine as well as the activity of the transporter, allowing greater carbohydrate absorption and oxidation during exercise. It is also likely that, when such adaptations occur, the chances of developing GI distress are smaller. Future studies should include more human studies and focus on a number of areas, including the most effective methods to induce gut adaptations and the timeline of adaptations. To develop effective strategies, a better understanding of the exact mechanisms underlying these adaptations is important. It is clear that "nutritional training" can improve gastric emptying and absorption and likely reduce the chances and/or severity of GI problems, thereby improving endurance performance as well as providing a better experience for the athlete. The gut is an important organ for endurance athletes and should be trained for the conditions in which it will be required to function.